Managing Halal Recreation Services for Quality of Life and Ecosystem in Brunei Darussalam - Nurulain Nabilah binti Hassan; Nurul Amal Shafeena binti Hasni; Dayangku Nazirah binti Pengiran Haji Ayub; Anis Malik Thoha; Noorhizrah binti Haji Muhammad (Journal of Islamic Economic Scholar, 2022)
Brunei Darussalam has a diverse ecosystem and is considered among the countries with high forest cover. The country’s natural vegetation is tropical evergreen rainforests estimated to be around 75 per cent of the country’s total land area and composed primarily of old-growth forests. However, solid policies and systems in the Brunei ecosystem need to speed up the transition to a resilient economy that promotes forest, sustainable land use, biodiversity, and climate goals. The management of halal recreation services for quality of life and ecosystem was the subject of this study. This study will look into the governments and private sector’s actions in managing halal recreation to improve the environment’s quality of life, assess individual initiatives and observe the ecosystem’s primary causes